2011
DOI: 10.1002/marc.201100272
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly Pluronic and β‐Cyclodextrin to Hollow Nanospheres for Enhanced Gene Delivery

Abstract: This paper studies a kind of hollow nanospheres prepared by self-assembly β-cyclodextrins (β-CDs) and poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (pluronic F127) for gene delivery. It was found that this kind of hollow nanospheres enable load PEI10K/DNA and the resulting F127NH2 βCD/(PEI10K/DNA) with 0.08 µg/well DNA display equal or higher gene delivery capability compared to PEI10K/DNA with 1 µg/well DNA in the absence or presence of serum. The cytotoxicity of the nanospheres was over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…One kind of nanoassembly was hollow nanospheres based on inclusion complexation between b-CD and PEG-PPG-PEG (F127), which could encapsulate PEI/DNA in the hollow core. 63,64 The resulting complexes displayed similar or more efficient gene transfection in comparison with PEI/DNA, but much less cytotoxicity. Another kind of nanoassembly was rod-like nanoparticles prepared by self-assembly of a-CD and PEG-PEI.…”
Section: Gene Deliverymentioning
confidence: 99%
“…One kind of nanoassembly was hollow nanospheres based on inclusion complexation between b-CD and PEG-PPG-PEG (F127), which could encapsulate PEI/DNA in the hollow core. 63,64 The resulting complexes displayed similar or more efficient gene transfection in comparison with PEI/DNA, but much less cytotoxicity. Another kind of nanoassembly was rod-like nanoparticles prepared by self-assembly of a-CD and PEG-PEI.…”
Section: Gene Deliverymentioning
confidence: 99%
“…It has been observed that the incorporation of drugs into the hydrophobic PO core of these micelles increases the solubility, metabolic stability and circulation time during its journey towards the target . However, very less studies are available showing the use of pluronic for gene delivery . It was observed that pluronic block copolymers increase the expression of pDNA in skeletal muscle in mice .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] Among the various supramolecular assemblies, CD-based (Pseudo) polyrotaxanes have been extensively studies for their uses as carriers in drug delivery, such as thermo-/pH-sensitive hydrogels, [33][34][35] vesicles and micelles, as carriers for the controlled drug release 36 and gene carriers. [37][38][39] However, (Pseudo) polyrotaxanes, self-assembled from cyclodextrins (CDs) and polyesters, were apt to form crystallized precipitate in most of the solvent, especially in water, which profoundly limited their development in biomedical applications. In this article, amphiphilic block copolymers with novel architecture, a pH-sensitive amphiphilic dendritic polyrotaxane polymer-drug conjugate (PR-g-DOX), were successfully developed through a highly efficient approach.…”
Section: Introductionmentioning
confidence: 99%